Development of holistic Islamic organisational culture model (I-Holismik) in Islamic banking institutions in Malaysia - Abd Rahman, Rosfazila; Abdul Hamid, Nor ‘Adha; Yaakob, Nor Azuwan; Zaini, Abdul Razif; Niteh, Muhammad Yosef; Ong, Jessica Hai Liaw; Abd Rahman, Rohizah (ASR Research India, 2022)
Islamic organisational culture is a set of values based on the Qur`an, Sunnah, Ijma and Qiyas that help the members of the organisation to understand the purpose of the organisation, how the organisation works and its interests. The practise of Islamic organisational culture through the Islamic Banking System (SPI) is a manifestation of the fundamental re-emergence of Islamic values in Islamic banks. The main objective of this study is to develop a holistic model of Islamic organisational culture that can be applied in banking institutions in Malaysia for the sustainability of organisational management. This qualitative study uses observation, documentation and interview methods to develop a detailed Islamic organisational culture model in Islamic banking institutions in Malaysia. The resulting data was then analysed using ATLAS.ti. The findings of the study suggest a holistic model of Islamic organisational culture that focuses on Islamic banking institutions as the medium and implementation site for organisational management sustainability. It is expected that the development of this new model will be a reference for Islamic banking institutions, especially in further strengthening the management of the organisation as well as in creating a holistic Islamic organisational culture that can directly enliven Islamic law in general.